12x * 4x2 = 48x3
4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x
4x2 + x2 = 8 + x2
sqrt(4x2) = Â± 2x
The GCF is 4x2.
1x8 2x4 4x2 4x2
4x2 - 2x = 0
2003 4x2 Gator
4x2 - 9y Not factorable from what I see.
4x2-y2 = (2x-y)(2x+y)
4x2 = 8, 8-9 = -1 therefore the answer is "-1"
(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)
In real numbers there is no square root of -4x2 However, when using complex numbers where √-1 = i, then: √-4x2 = 2xi If you were asking, for example, with regard to the difference of two squares, eg y2 - 4x2, then you are actually finding the square root of 4x2 which is 2x, giving: y2 - 4x2 = (y + 2x)(y - 2x)
If that's + 4x2, the answer is 2x(x2 + 2x - 4)
4x2-x+2x2 is 6x2-x when simplified
4x2-2x-12 = (2x+3)(2x-4)
4x2-4x+1 = (2x-1)(2x-1)
4x2 plus 3=11
4x2 - 23xy + 15y2 = (4x - 3y)(x - 5y)